Vulnerability Assessment of Crop Husbandry due to Drought in North- Western Region of Bangladesh - Rahaman, H; Sarker, M A; Rahman, M Z; Momin, M R; Raihan, M L (Journal of Environmental Science and Natural Resources, 2025)
Drought is a natural phenomenon linked to reduced rainfall, affecting crop husbandry in Mediterranean semi-arid conditions like the northwestern region of Bangladesh. A study was conducted in three upazilas, Chapainawabganj Sadar, Lalpur, and Godagari, involving 180 farmers. The results showed that most farmers had a vulnerability level ranging from slightly to moderately vulnerable to crops. However, a small number of people were in low vulnerability, indicating they practiced coping strategies during drought severity. The vulnerability of crops increased with exposure and sensitivity index and lower adaptive capacity. The study found that farmers experienced high severity of drought, with 78.9% experiencing medium effects, crop damage, high irrigation costs, and low income. To reduce crop vulnerability, the government and development agencies should provide technical support, such as re excavation of ponds and canals, rainwater storage facilities, new irrigation projects, extension services, education, income-generating opportunities, and water conservation measures. This will help reduce the vulnerability of crops to drought and improve crop management. Environ. Sci. & Natural Resources, 14(1&2): 72-80, 2025